Gender-specific health literacy of individuals with a migrant background: A mixed-method approach. (13th November 2019) - Aldin, A; Chakraverty, D; Baumeister, A; Monsef, I; Jakob, T; Seven, ÜS; Anapa, G; Kalbe, E; Woopen, C; Skoetz, N
Abstract: Background: The project "Gender-specific health literacy in individuals with a migrant background (GLIM)" (German Federal Ministry of Education and Research; 01GL1723) aims to provide a comprehensive overview of international research and evidence on aspects of gender and migration related to health literacy. It encompasses primary and secondary research using a mixed-methods approach. Methods: In a first step, we systematically review the available quantitative and qualitative evidence: in the first quantitative review, we meta-analyse the evidence on gender differences in health literacy of migrants. The second quantitative review assesses the effectiveness of interventions for improving health literacy in female and male migrants. The third review summarises qualitative evidence to assess factors associated with gender and migration that may play a role in the design, delivery, and effectiveness of such interventions. In a second step, we conduct primary research by performing focus group discussions (FGDs) with health care providers who regularly work with different migrant groups in order to explore their perspectives on the challenges and needs of migrants in the German health care system. Results: To date, we identified 163 relevant references after screening of 17, 932 references, for all reviews combined. Various health literacy interventions and measurement tools exist and require critical evaluation. The FGDs yielded hints to factors that a) influence gender differences in the health literacy of migrants (e.g. masculinity norms preventing Mediterranean men from consulting psychotherapists) or b) limit systemic health literacy (e.g. lack of translators). Conclusions: Results from the FGDs can provide insights into the processes underlying the results of the reviews. However, despite increasing research, summarising the available evidence is highly challenging, as there are no universal definitions of the key concepts health literacy and migrant background. Key messages: This is an interdisciplinary project, combining quantitative and qualitative evidence to provide maximum value to health policy and decision-making for the health care and health literacy of migrants. Research on gender-, and migration-specific aspects of health literacy is of great importance for the development and delivery of effective interventions for improving migrants' health literacy.